Transmitted blood infections and emerging vector-borne diseases in blood donors in northern Portugal - Ana Mota; Margarida Fonseca Cardoso (Hematology, Transfusion and Cell Therapy)
Background: Screening of transfusion-transmissible infectious agents of blood components is carried out in order to guarantee the safety of the transfusion process. The objective of this investigation was to characterize cases positive for transfusion-transmissible infectious agents in blood donations in the North of Portugal. Method: Data from 2010 to 2022 of the Local Health Unit-Santo Antonio were used for this study. In specific epidemiological situations, malaria, Chagas disease and West Nile virus were screened. Main results: Over 12 years, the health unit, received 137,751 donations with 108 positive tests. The proportions of human immunodeficiency viruses, syphilis, human hepatitis viruses type B and C varied between 0 and 44/100,000 donations. In this period, two cases of malaria were detected in 2020–2021, and 21 were detected in 2022 corresponding to 52.1/1000 donations screened. In 2022, two cases of Chagas disease and no cases of West Nile virus were detected. Conclusion: These results highlight the importance of a rigorous investigation at the time of donation in which the donor's history, including origin and movement in areas of greater geographic risk, are assessed. The recent and increasing detection of cases of malaria and Chagas disease confirms the presence of emerging infectious diseases transmitted by vectors, including mosquitoes, in blood donors. The increased risk of vector-borne diseases in Europe is a public health problem and represents a new challenge in screening donations.